Maldives : Report on Observance of Standards and Codes: FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2012)
The financial sector of the Maldives, although small and not developed, is susceptible to both money laundering and, to a lesser extent, terrorist financing. This report focuses on observance of standards and codes for the FATF-40 (Financial Action Task Force) recommendations for antimoney laundering (AML) and nine special recommendations on combating the financing of terrorism (CFT) in the Maldives. It provides a summary of the AML/CFT measures in place in the Maldives and contains recommendations on how the AML/CFT system could be strengthened.